Optimizing Employee Productivity: The Influence of Work Discipline and Compensation at Harper Perintis Hotel - Rostini, Rostini; syahribulan, syahribulan; Nasir, Muhammad; Arjang, Mardia, (Program Pascasarjana STIE Amkop Makassar, 2024)
Work discipline serves as the main foundation to build a structured and effective work environment. Employees who demonstrate discipline typically adhere to company rules and procedures, thus minimizing the possibility of inactivity or disruptions in the workflow. Conversely, a fair compensation system that aligns with employees' contributions significantly affects work productivity. In the hospitality industry, fostering a strong work ethic and providing competitive compensation are crucial in enhancing employee effectiveness. This study examines the impact of compensation and work discipline on employee productivity at Aston's Harper Perintis Makassar Hotel. Descriptive analysis, utilizing regression analysis and the coefficient of determination, is employed in this research. Primary data is collected through direct observation and questionnaires, while secondary data is sourced from relevant company documents. The research findings indicate a significant relationship between work discipline and employee productivity at Harper Perintis Hotel. Employees who exhibit high levels of work discipline tend to achieve superior productivity. Moreover, the findings also demonstrate that employee perceptions regarding the compensation system have a positive and significant influence on work productivity. To advance organizational objectives and enhance work productivity, management should prioritize fostering work discipline and ensuring adequate compensation for employees. Keywords: work discipline, compensation, employee productivity, hospitality industry